J. M. Coetzee: politics of the child, politics of nonposition. Issue 6 (2nd June 2020) - Hu, Xiaoran
ABSTRACT: This article explores the political resonance of the child figure in J. M. Coetzee's writing by linking the two child characters in his fictional memoir Boyhood (1997) and his recent fiction The Childhood of Jesus (2013). Mirroring some recurring themes and motifs in Coetzee's early novels, the trope of childhood and the issue of education, as I observe, have become increasingly important, since the late and post-apartheid era, in the author's ongoing critique of colonialist and neocolonialist forms of power. This article will discuss the ideological dimension and the subversive potentiality embedded in this particular literary trope through the concept of political 'nonposition'. Developed by Coetzee himself in his critical essays and often associated with the trope of the child, the notion of 'nonposition' is significant to understand Coetzee's novelistic discourse as a form of non-sectarian political participation. Tracing Coetzee's Australian-phase writing back to post-apartheid South Africa, this article also illuminates part of a continuous trajectory in Coetzee's oeuvre that will shed light on the politics of his highly self-reflexive metafictional literary practice in general, which has been substantially informed by South African history and politics preceding his emigration to Australia and the development of his late style.